Accounting for Natural Resources: The Nigerian Experience - Bassey, Bassey E.; Bessong, K. Peter; Ojong, Oben V.; Effiong, G. Tony (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2019)
Nigeria is a country immensely blessed with various natural resources some of which have been and are being explored; some others have not yet been explored. However, the potential benefits of those resources to the nation and citizenry are far from realized for the larger part of the population. In this light, the study was designed to examine how natural resources accounting can be used to benefit Nigeria as a nation and its citizenry. Two (2) research questions that equally reflect the two key variables in the hypotheses were formulated to guide the study. Relevant literature to buttress and illuminate the work was reviewed. The comparative advantage theory was adopted side-by-side to explain, analyze, and possibly predict the outcome of the study. The survey method, a form of descriptive design was deployed as the main methodological tool to navigate the study. Both primary and secondary sources of data were considered relevant for material sourcing. The Pearson Correlation Coefficient analysis was considered as a method for measuring, testing, and analyzing the key hypothetical variables in the study. The findings reveal that natural resources accounting could significantly impact upon nation’s development. Based on the findings of the study, recommendations were made.